Dimensions influencing service quality of Arabic restaurant towards customer satisfaction in Selangor / Muhammad Arif Jaafar - Jaafar, Muhammad Arif (Faculty of Business and Management, 2019)
Intense competition in the business environment forces company to look for the best approach to attract and create customer satisfaction. Service quality is a strategy used by many companies to maintain customer satisfaction. Good implementation of service quality strategies will result in quality built between customers and company. The main study of this research is to investigate the influence of service quality dimension of Arabic restaurant towards customer satisfaction in Selangor. Customer satisfaction being a dependent variable in this research and measured by five independent variables which is tangible, reliability, responsiveness, assurance and empathy. A review of literature was conducted to find out the relationship between service quality and customer satisfaction on Arabic restaurant. The literature review confirms this relationship. This research is based on 102 respondents which are the customer of Arabic restaurant in Selangor. Sampling method used in this study is convenience sampling. The data was analysed using correlation coefficient and regression by using SPSS software. The findings reveal there is a positive relationship between the service quality dimension which is tangible towards customer satisfaction.